Pelatihan First Aid untuk Meningkatkan Sikap dan Pengetahuan Guru di Sekolah Dasar - Ristina Mirwanti; Aan Nuraeni (Universitas Muhammadiyah Pringsewu, 2017)
We often found emergency condition on children in elementary school which can lead death. Teachers should have good knowledge and favorable attitude toward first aid so they can give right intervention on emergency condition. The objective of this activity was to improve attitude and knowledge of elementary school teachers toward it. This activity be held on training program includes lecture, discussion, and practice. Result showed there was any improvement of elementary school teachers’ attitude and knowledge score. Reevaluation and retraining should be held to improve significant score of teachers’ attitude and knowledge so do their skill toward first aid on children emergency condition in elementary school.Keywords: first aid, emergency condition, elementary school teachers, children